The Effect of Clothing on the Rate of Decomposition and Diptera Colonization on Sus scrofa Carcasses. Issue 4 (31st March 2015) - Card, Allison; Cross, Peter; Moffatt, Colin; Simmons, Tal
Abstract Twenty Sus scrofa carcasses were used to study the effect the presence of clothing had on decomposition rate and colonization locations of Diptera species; 10 unclothed control carcasses were compared to 10 clothed experimental carcasses over 58 days. Data collection occurred at regular accumulated degree day intervals; the level of decomposition as Total Body Score (TBSsurf), pattern of decomposition, and Diptera present was documented. Results indicated a statistically significant difference in the rate of decomposition, (t427 = 2.59, p = 0.010), with unclothed carcasses decomposing faster than clothed carcasses. However, the overall decomposition rates from each carcass group are too similar to separate when applying a 95% CI, which means that, although statistically significant, from a practical forensic point of view they are not sufficiently dissimilar as to warrant the application of different formulae to estimate the postmortem interval. Further results demonstrated clothing provided blow flies with additional colonization locations.